Diffuse idiopathic skeletal hyperostosis of the spine - Gustaw Wójcik; Anna Szulc (Journal of Education, Health and Sport, 2018)
Spontaneous hyperostosis of the spine is a degenerative disease with a non-inflammatory base consisting in the formation of bone growth with thickening, calcification and ossification of soft tissues surrounding at least four vertebral bodies and three disc spaces. The part of the spine covered by these changes take the shape of stearin burning after the candle - this symptom is visible in X-ray images. The disease especially affects the elderly. Symptoms of the disease are associated with stiffness of the spine and chronic pain. The principle of comprehensive treatment applies to the treatment of hyperostosis. In addition to pharmacotherapy, physiotherapy is widely used (kinesitherapy, electrotherapy, thermotherapy), a properly balanced diet and psychotherapy, and in extreme cases such as dysphagia, compression and spine stenosis, surgical procedures are implemented to remove pathologically grown bone tissue.